Ethics in Consumer Choice An Empirical Analysis based on the Example of Coffee - Langen, Nina.; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2013)
Individuals have a multitude of possibilities by means of their decisions to influence ecological, social and economic developments at the regional, national and global level. Nina Langen elaborates differences and similarities of forms of ethical behaviour, such as ethical consumption and charitable giving in general and investigates whether German consumers differentiate between different types of ethical behaviour in particular. Choice experiment, latent class analysis, information display matrix and item-based attitude assessment allow the comparison of stated and revealed preferences as well as an analysis of the relevance of ethical product features within the context of different product and process attributes. The dissertation provides insights into a research field that becomes more and more relevant and improves the understanding of the interdependencies as well as consumers’ assessment of the possibilities of ethical behaviour.     Der Inhalt n  Consumers‘ Decision Making n  Possibilities of Ethical Behaviour n  Relevance of Fair Trade, Organic Production and Cause-Related Marketing for Product Selection n  Acceptance and Critical Success Factors of Cause-Related Marketing in Germany     Die Zielgruppen ·         Researchers and students in the fields of business, marketing and agricultural economics ·         Executives and consultants in commercial enterprises as well as non-profit organisations and non-governmental organisations focusing on ethical consumption, fair trade, donations, corporate social responsibility, and cause-related marketing      Die AutorIn Dr. Nina Langen obtained her Ph.D. in agricultural economics from the University of Bonn. She conducted her Ph.D. studies at the Center for Development Research in the Department of Economic and Technological Change and at the Institute for Food and Resource Economics in the Department of Agricultural and Food Market Research, both at the University of Bonn.
Consumers’ decision making -- Preference measurement -- Ethical consumption -- Fair Trade -- Charitable Giving -- Cause-related Marketing.
Keywords: Marketing; Marketing